2003
DOI: 10.1177/097215090300400201
|View full text |Cite
|
Sign up to set email alerts
|

Designing Innovative Organizations in Malaysia: Do Structure and Culture Matter?

Abstract: The purpose of this article is to determine the influence of organizational structure (formalization and centralization and culture (participative decision-making, support and collaboration, learning and development) on innovation (technological and process, administrative, product and overall) among firms operating in Malaysia. Regression analyses of 123 responses revealed that only cultural variables have positive effects on two forms of innovation (technological and process, and administrative). Specificall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 45 publications
1
12
2
Order By: Relevance
“…The finding associated to the positive impact of adhocracy culture is consistent with those of previous studies (Cameron and Quinn, 2011). The existence of a strong and positive relationship between the firm's culture and innovativeness is also consistent with Jantan et al (2003) who examine the influence of culture and structure on innovativeness among manufacturing and service companies operating in Malaysia and further find out that the structural components of these firms do not have any significant impact on the organizational innovativeness. Similarly, the existence of a positive relationship between market orientation and innovativeness as discovered in the current study is consistent with previous studies (for example Jaworski and Kohli (1993).…”
Section: Resultssupporting
confidence: 57%
See 3 more Smart Citations
“…The finding associated to the positive impact of adhocracy culture is consistent with those of previous studies (Cameron and Quinn, 2011). The existence of a strong and positive relationship between the firm's culture and innovativeness is also consistent with Jantan et al (2003) who examine the influence of culture and structure on innovativeness among manufacturing and service companies operating in Malaysia and further find out that the structural components of these firms do not have any significant impact on the organizational innovativeness. Similarly, the existence of a positive relationship between market orientation and innovativeness as discovered in the current study is consistent with previous studies (for example Jaworski and Kohli (1993).…”
Section: Resultssupporting
confidence: 57%
“…Moreover, previous researches suggest that several characteristics will influence the innovativeness of a firm (Katz and Allen, 2004). There is however inconsistency in some of these results (Jantan et al, 2003). For example, while previous studies have shown that organizational culture influences innovativeness (Hurley and Hult, 1998), recently, Yusof and Abidin (2011) find that culture does not significantly influence the innovativeness among Malaysian public-listed housing developers.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The term participative decision-making has been associated with other terms, such as empowerment, involvement, engagement and consultation (Jantan, Nasurdin, and Ahmed Fadzil 2003). Empowerment is commonly described in terms of the employee's self-control, freedom and autonomy over his or her work and responsibility for decision-making (Mullins 2002).…”
Section: W Satsomboon and O Pruetipibulthammentioning
confidence: 99%